PENDAMPINGAN MANAJEMEN BISNIS DALAM PENERAPAN GREEN BUSINESS UMKM BATIK ECO PRINT DI KABUPATEN BOJONEGORO - Joko Hadi Susilo; Hartiningsih Astuti; Anggita Munawaroh; Ananda Marda Fitria (Jurnal Abdi Masyarakat, 2026)
The mentoring program for Eco-Printed Batik MSMEs in Bojonegoro Regency was conducted due to the low level of implementation of sustainable business management based on green business. Partners face obstacles such as minimal product innovation, suboptimal digital marketing, and conventional business management. These conditions limit competitiveness and hinder business sustainability. The mentoring program aims to increase the capacity of MSMEs to implement green innovation, green marketing, and green management to make their businesses more adaptive and competitive. The program is implemented through field observation, training, direct mentoring, and a participatory approach. The mentoring focuses on developing innovative natural product ingredients, strengthening environmentally friendly digital marketing, and improving business management through simplified record-keeping and resource efficiency. The results of the program demonstrate an increase in the understanding and skills of MSMEs in developing product variations, utilizing social media for promotion, and implementing more structured business management. This program supports the Tri Dharma of Higher Education and encourages an environmentally-based creative economy in Bojonegoro.